Metformin modulates IL-8, IL-1β, ICAM and IGFBP-1 expression in human endometrial stromal cells - Germeyer, Ariane; Jauckus, Julia; Zorn, Markus; Toth, Bettina; Capp, Edison; Strowitzki, Thomas (Reproductive biomedicine online, 2011)
To evaluate the effects of metformin on endometrial stromal cell gene expression and on the decidualization process, endometrial biopsies were collected from five healthy, regularly cycling women. Stromal cell culture was performed and decidualized with oestrogen/progesterone in the presence or absence of metformin and thereafter stimulated with insulin. The effect of metformin on decidualization was analysed by prolactin determination in the cell culture supernatant. Gene expression of insulin-like growth factor binding protein 1 (IGFBP-1), interleukin (IL) 8 and 1β and intercellular adhesion molecule (ICAM) was analysed by real-time PCR. Decidualization was significantly diminished in cells incubated with metformin (P<0.05) accompanied by a significant reduction of prolactin secretion in the supernatant (day 10: 2.2 fold, P<0.05; day 15: 3.1 fold, P<0.05). IGFBP-1 gene expression was reduced after long-term metformin exposure (7.7 fold, P<0.05). The negative effect of insulin on IL-8 (4.8 fold) and IL-1β (9.3 fold) gene expression was similarly found in cells incubated with metformin. As far as is known, this is the first demonstration of a change in endometrial gene and protein expression after in-vitro stimulation with metformin, including a diminished decidualization process and changes in genes relevant to implantation. This study evaluated the effects of metformin (an antidiabetic drug) on cells of the inner lining of the uterus (stromal cells) and their process of transformation, called decidualization, as well as their gene expression during implantation. Stromal cell culture was performed and cells were stimulated with oestrogen/progesterone in the presence or absence of metformin. Effects of metformin on decidualization were analysed by prolactin, a decidualization marker, in stromal cell culture supernatant. Furthermore, gene expression of insulin-like growth factor binding protein 1 (IGFBP1), interleukin (IL) 8 and 1β and intercellular adhesion molecule (ICAM) before and after insulin stimulation was analysed by quantitative real-time polymerase chain reaction. Over time, decidualization was significantly diminished in cells incubated with metformin leading to a 3.1 fold reduction after 15 days (P<0.05). IGFBP-1 gene expression was reduced after long-term metformin exposure (7.7 fold, P<0.05). Looking at implantation markers, 48-h metformin incubation increases IL-8 gene expression (31.1 fold, P=0.059) and IL-1β gene expression (8.2 fold, P<0.05), while it does not change ICAM gene expression. The negative effect of insulin on IL-8 (4.8 fold) and IL-1β (9.3 fold) gene expression was similarly found in cells incubated with metformin. We were able to show for the first time a change in endometrial gene and protein expression after in-vitro stimulation with metformin, including a diminished decidualization process and changes in genes relevant to implantation. This may potentially affect the rate of implantation as well as pregnancy outcome in women under metformin treatment.
Gesehen am 09.11.2023
Online verfügbar ab 14. November 2010